Isolation of a 29.5 kb Plasmid conferring Multiple Drug Resistance in Pseudomonas aeruginosa - Begum, Shahanara; Ahmed, Iftikhar; Alam, Faisal; Samsuzzaman, M; Hassan, Parvez; Absar, Nurul; Haq, Jalaluddin Ashraful (Journal of Bio-Science, 2011)
Context: Worldwide emergence of plasmid mediated multi drug resistant bacterial strain is a growing concern, especially in hospital infections caused by Pseudomonas aeruginosa. Relation of plasmid and drug resistance in clinical isolates of P. aeruginosa by curing and transformation experiments is scanty. Objectives: To isolate, purify and characterize plasmid DNA harbored in a selected Pseudomonas aeruginosa strain encoding multiple drug resistance and to perform transformation of the isolated plasmid into a sensitive strain of Escherichia coli LE 392 to judge transformation potential of the donor P. aeruginosa strain. Materials and Methods: Plasmid DNA was isolated from a multidrug-resistant (MDR) strain of P. aeruginosa obtained from swab of a hospitalized burn patient by mini-scale method. DNA was purified, quantitatively estimated and electrophoresed on 0.8% agarose gel. Transformation was done as per Cohen and co-workers using plasmid DNA isolated from MDR P. aeruginosa strain as the donor and the E. coli LE 392 strain. The presence of plasmid in transformants checked through electrophoresis and the transformants was also tested for each drug resistance already recorded for the donor strain by disc diffusion method and again confirmed by spreading its culture on the selected antibiotic plate of different concentrations. Results: A single plasmid of nearly 29.5 kb mass was isolated from MDR P. aeruginosa strain from clinical swab. This plasmid was transferred into sensitive and plasmid lacking recipient E. coli LE 392. Subsequent experiments on the transformed strain revealed that it acquired MDR and harbored a 29.5 kb plasmid which resembled to that of the donor strain proving that it encodes transferable MDR. Conclusion: The MDR P. aeruginosa strain contained a transferable plasmid conferring resistance to ampicillin, chloramphenicol, cotrimoxazole, tetracycline and ciprofloxacin. Key words: Pseudomonas aeruginosa; Multidrug–resistance; plasmid isolation; transformation. DOI: 10.3329/jbs.v17i0.7113 J. bio-sci. 17: 95-100, 2009